Parásitos causantes de infección intestinal en residentes de San Rafael, parroquia San Andrés, Guano, Chimborazo, 2022 - Proaño Valverde, Jazmine Micaela (2023)
ABSTRACT Intestinal parasitosis is a public health issue, particularly in developing countries, affecting the most vulnerable populations in rural and poor urban areas. The current study achieved its goal of investigating the parasites that cause intestinal infection in residents in the community of San Rafael, San Andrés parish, Guano-Chimborazo, applying parasitological diagnostic techniques to calculate parasite prevalence. The type of research applied in the methodology was descriptive with a field/non-experimental design of prospective chronology with a quantitative approach; 252 residents of San Rafael were part of the population, 46 of them provided their fecal samples (21 men and 25 women). Data were collected by means of coprological sampling and by applying surveys to adults and minors. The prevalence of parasitic species present in children and adults in the community of San Rafael is detailed, most individuals presented three species (31,11%) (X2= 8,622 p=< 0,0001), followed by two species (24,44%) and four species (17,78%). The female sex presented a higher frequency of Blastocystis sp. (100%) (X2= 5.215 p= 0,0224), Endolimax nana (84%) (X2= 4,060 p= 0.0439) and Entamoeba coli 36% (EF p= 0,0132) with respect to the male sex, showing percentage differences that reached statistical significance. It is important to mention that the only helminth detected was Hymenolepis nana (2,17%). In conclusion, in the rural community studied, the population is characterized by a lack of knowledge of sanitary measures and inadequate eating habits, favoring the transmission of enteroparasites. Key words: Intestinal infection, parasitic species, prevalence, Blastocystis sp, Endolimax nana, Entamoeba coli, Hymenolepis nana. Reviewed by: Mg. Mishell Salao Espinoza ENGLISH PROFESSOR C.C. 0650151566 Firmado electrónicamente por: MISHELL GABRIELA SALAO ESPINOZA